KEEFEKTIFAN MODEL PEMBELAJARAN QUANTUM (QUANTUM TEACHING) TERHADAP HASIL BELAJAR MATA PELAJARAN IPS SISWA KELAS IV SDN REJOSARI 02 SEMARANG KECAMATAN SEMARANG TIMUR - Tulus Widya Astuti; Sunan Baedhowi; M Yusuf Setia W (STKIP Subang, 2022)
This study aims to determine the effectiveness of the application of the Quantum Teaching learning model on the learning outcomes of social studies subjects for fourth grade students of SDN Rejosari 02 Semarang. The research used Quasy Experimental Design in the form of Pretest-Posttest Control Group Design. While the population used by this researcher is all class IV A and class IV B SDN Rejosari 02 Semarang. The sample used is the fourth grade students of SDN Rejosari 02 Semarang taken from the saturated sampling technique. From the data, the students' scores increased with an average posttest score of 86.8 for the experimental class and 69.8 for the control class. So it can be concluded that the Quatum Teaching learning model is effective in improving the learning outcomes of fourth grade students at SDN Rejosari 02 Semarang.